La inclusión educativa y su influencia en el desarrollo cognitivo de las niñas de cinco años de edad con discapacidad de la escuela “Zoila Alvarado”, de la ciudad de Loja, periodo lectivo 2014 – 2015. Lineamientos propositivos - Rojas Luzuariaga, Any Paola (2015)
The present work of investigation titled:” THE EDUCATIONAL INCORPORATION AND HIS INFLUENCE IN THE COGNITIVE DEVELOPMENT OF THE FIVE-YEAR-OLD GIRLS OF AGE WITH DISABILITY OF THE SCHOOL “ZOILA ALVARADO ", GIVES LOJA's CITY, SCHOOL PERIOD 2014 - 2015. PROPOSED LIMITS". It is structures on the basis of the in force Limits of Graduation in Loja's National University. Since general objetive considered " To determine the Educational Incorporation and his incident in the Cognitive Development of the five-year-old girls of age with disability, of the School "Zoila Alvarado" of Loja's city. " To achieve his fulfillment also there appeared specific, such objetives as: 1. To identify the type of disability that the five-year-old girls of age present with disability, of the School "Zoila Alvarado", of Loja's city, school period 2014 - 2015. Proposed Limits.; 2. To establish the strategies of Educational Incorporation that apply the docentes of the five-year-old girls of age with disability, of the School "Zoila Alvarado", of Loja's city, school period 2014 - 2015. Proposed Limits.; and 3. To value the Cognitive Development of the five-year-old girls of age with disability, of the School "Zoila Alvarado", of Loja's city, school period 2014 - 2015. Proposed Limits. To develop each of the raised aims one came to the utilization of such diverse methods as: scientific, inductive and deductive Method; the applied Technologies were those of survey, applied to the teachers of the lounges of the IInd Level of Initial Education with the purpose of determining the process of education - learning with the five-year-old girls who have disability, Test of Cognitive Skills applied to the five-year-old girls with disability of the School "Zoila Alvarado" to evaluate the Cognitive Development; and the technology of the Observation to know the process of education - learning given in the classes. Finally by means of the results obtained of the surveys realized to teachers characteristics were stated with regard to the education - learning of the five-year-old girls of The Initial IInd, as for the participation of these girls it was found that in 33 % it is active, whereas in 67 % it is passive; the methodology used by teachers is diverse and if it gives them good results to achieve the education that these girls need, between the methodology that they use one finds the use of audio-visual material; in addition the advisers' existence was stated pedagogically that help the teachers for the education of the girls with disability. The results of the Test of Functions of the Cognitive Development applied to the girls with disability it threw positive results in 67 % and negatives in 33 % what indicates a satisfactory achievement of learnings given in the lounge of class.